THE ROLE OF RELIGIOSITY IN INFLUENCING THE KNOWLEDGE AND SOCIAL ENVIRONMENT OF SAVINGS INTEREST - Pranata, Ahmad Adi; Rahayu, Yayuk Sri (I-Finance Journal, 2023)
The aim of this research is to analyze the influence of knowledge, social environment and religiosity on interest in saving in Islamic banks. The research methodology used is quantitative with experimental techniques to test the impact of knowledge and social environment on students' tendencies to practice saving religiously as a mediating factor. The population of this study consisted of students registered at the Faculty of Economics, UIN Malang, with a total of 2494 individuals, and the sample used was 147 students selected using purposive sampling. Data was collected through a Google Form questionnaire which contained statements related to research variables. The research results show that knowledge, social environment, and religiosity have a significant influence on interest in saving in Islamic banks. The conclusion of this research is that these factors can be important considerations in understanding savings behavior in Islamic banks, so they need to be considered in developing marketing strategies and sharia financial education.